A facile route to fabricate a biodegradable hydrogel for controlled pesticide release1. Issue 18 (5th March 2015) - Sheng, Wenbo; Ma, Shuanhong; Li, Wei; Liu, Zhiqing; Guo, Xuhong; Jia, Xin
<x xml:space="preserve">Abstract</x> An environmentally friendly hydrogel induced by hydrazone bond formation can be triggered with the temperature and pH to achieve controllable avermectin release.